Impedimetric Dengue Biosensor based on Functionalized Graphene Oxide Wrapped Silica Particles. (10th March 2016) - Jin, Seon-Ah; Poudyal, Shishir; Marinero, Ernesto E.; Kuhn, Richard J.; Stanciu, Lia A.
Highlights: 3D graphene oxide based material design. Fabrication of a label-free dengue DNA and RNA impedimetric biosensor. Design of a surface-based dengue sensor with good selectivity and detection limit. Abstract: A composite of 3-Aminopropyltriethoxysilane (APTES) functionalized graphene oxide (APTES-GO) wrapped on SiO2 particles (SiO2 @APTES-GO) was prepared via self-assembly. Transmission electron microscopy (TEM) and ATR-Fourier Transform Infrared spectroscopy (ATR-FTIR) confirmed wrapping of the SiO2 particles by the APTES-GO sheets. An impedimetric biosensor was constructed and used to sensitively detect dengue DNA and dengue RNA via primer hybridization using different oligonucleotide sequences. The results demonstrated that the SiO2 @APTES-GO electrode material led to enhanced dengue RNA detection sensitivity with selectivity and detection limit (1 femto-Molar), compared to both APTES-GO and APTES-SiO2 . The three-dimensional structure, higher contact area, electrical properties and the ability for rapid hybridization offered by the SiO2 @APTES-GO led to the successful design of a dengue biosensor with the lowest detection limit reported to date.